2019
DOI: 10.1111/lasr.12439
|View full text |Cite
|
Sign up to set email alerts
|

Workers with Disabilities Between Legal Changes and Persisting Exclusion: How Contradictory Rights Shape Legal Mobilization

Abstract: It has become commonplace within disability sociolegal scholarship to argue that, in the last 30 years, a new legal and policy approach to disability has emerged, leading to a paradigm shift from a social protection framework to an antidiscrimination model. Some authors have stressed, however, that the new model has not fully replaced the older social protection approach. Yet little is still known about how the coexistence of these different models impacts on the everyday experience of disability in the workpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…The extant literature documents that workers might have broadly different preferences (e.g., research on workers' variation in desired changes to their workplaces and industries by Trautner et al [2013]; McCann's study of variations in employees' mobilization around different workplace rights [1994]; or Reynolds and May's [2014] research on how mothers' religious identities affect their preferences for number of hours worked). However, employee variation in the assessment of specific accommodations in the workplace is rarely considered (for exceptions, see Hodson, 2001; Lejeune & Ringelheim, 2019; Marshall, 2005). As this article's data show, some lactating employees might want accommodations to help them stay productively engaged during their lactation breaks, while others might want lactation rooms to facilitate relaxation and reconnecting with their families.…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature documents that workers might have broadly different preferences (e.g., research on workers' variation in desired changes to their workplaces and industries by Trautner et al [2013]; McCann's study of variations in employees' mobilization around different workplace rights [1994]; or Reynolds and May's [2014] research on how mothers' religious identities affect their preferences for number of hours worked). However, employee variation in the assessment of specific accommodations in the workplace is rarely considered (for exceptions, see Hodson, 2001; Lejeune & Ringelheim, 2019; Marshall, 2005). As this article's data show, some lactating employees might want accommodations to help them stay productively engaged during their lactation breaks, while others might want lactation rooms to facilitate relaxation and reconnecting with their families.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of EU law, this could (for example) pertain to the way in which EU law is viewed and consequently acted upon. Other research has pointed to the relevance of framing as well, by speaking of the ‘perception’ of litigants when deciding to mobilise or not to mobilise the law (Lejeune and Ringelheim, 2019, 2022).…”
Section: Political/legal Opportunity Structures Agent Characteristics...mentioning
confidence: 99%
“…Various studies have explored how the social characteristic of those involved in the conflicts influence legal mobilisation. They have shown that some specific groups have a lower ability to assert their rights, such as those who experience discrimination (Bumiller, 1987;Clermont and Schwab, 2004), women in situations of sexual harassment (Marshall, 2005) or people with disabilities (Engel and Munger, 2003;Lejeune and Ringelheim, 2019). Later, Nielsen (2000) and Morrill, Edelman, Tyson and Arum (2010) showed that people react differently to an offence depending on their race or gender.…”
Section: The Dispute Pyramidmentioning
confidence: 99%